Destruction of Images as a Total Work of Art. The Gesamtkunstwerk as Black Hole - El-Mecky, Nausikaä (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2021)
The destruction of images is a process that often produces a new imaginary, a visual spectacle in itself. Even after the original image has been obliterated, its absence can create its own powerful aesthetic that survives centuries. The article focuses on two historical case studies: the iconoclasm in Zurich in the 1520s and the National Socialist attack on so-called degenerate art. Through these, it aims to show how destruction can yield a total work of art through a carefully planned, even scripted, process that is far removed from the «lunatic running around with a sledgehammer» stereotype. It argues that many attacks on images are characterised by transformation, mysticism and performativity, during which a careful oscillation between absence and presence plays an important role. Ultimately, this contribution strives to create a new understanding of destructions of images through the frame of the Gesamtkunstwerk.